Anticoagulation for valvular heart disease in community-based practice - Rose, Adam J.; Ozonoff, Al; Henault, Lori E.; Hylek, Elaine M. (Thrombosis and Haemostasis, 2010)
Little is known about patients who receive oral anticoagulation for valvular heart disease (VHD) in community-based practice. It was this study’s objective to describe the characteristics, management, and outcomes of patients anticoagulated for VHD, compared to patients anticoagulated for atrial fibrillation (AF). We used a nationally-representative cohort of community-based anticoagulation care in the United States. Data collected included indications for therapy, demographics, selected comorbid conditions, international normalised ratio (INR) target ranges, INR control, and clinical outcomes. We identified 1,057 patients anticoagulated for VHD (15.6% of the overall cohort) and 3,396 patients anticoagulated for AF (50.2%). INR variability was similar between the two groups (0.64 vs. 0.69, p = 0.80). Among patients with aortic VHD, for whom a standard (2–3) target INR range is recommended, 461 (84%) had a high target range (2.5–3.5), while 95 (16%) had a standard target range. VHD patients had a higher rate of major haemorrhage compared to AF patients (3.57 vs. 1.78 events per 100 patient-years, incidence rate ratio 2.02, 95% CI 1.33 – 3.06). The rate of stroke/systemic embolus was similar between groups (0.67 vs. 0.97 events per 100 patient-years, incidence rate ratio 0.71, 95% CI 0.32 – 1.57). In our community-based study, approximately 15.6% of patients receiving warfarin were anticoagulated for VHD. VHD patients achieved similar anticoagulation control to patients with AF, as measured by INR variability. Nevertheless, the rate of major haemorrhage was elevated among VHD patients compared to AF patients; this finding requires further investigation.Disclaimer: The opinions expressed in this manuscript do not necessarily represent the views or policies of the United States Department of Veterans Affairs.
Keywords: Warfarin; anticoagulants; quality of health care; heart valve diseases